Laparoscopic sleeve gastrectomy for morbidly obese adolescents in Singapore - Dargan, Dallan (SINGAPORE MEDICAL ASSOC, 2023)
19th World Congress of the International-Federation-for-the-Surgery-of-Obesity-and-Metabolic-Disorders (IFSO)